Nanosystems for the Encapsulation of Natural Products: The Case of Chitosan Biopolymer as a Matrix - Anastasia Detsi; Eleni Kavetsou; Ioanna Kostopoulou; Ioanna Pitterou; Antonella Rozaria Nefeli Pontillo; Andromachi Tzani; Paris Christodoulou; Aristeia Siliachli; Panagiotis Zoumpoulakis (MDPI AG, 2020)
Chitosan is a cationic natural polysaccharide, which has emerged as an increasingly interesting biomaterialover the past few years. It constitutes a novel perspective in drug delivery systems and nanocarriers' formulations due to its beneficial properties, including biocompatibility, biodegradability and low toxicity. The potentiality of chemical or enzymatic modifications of the biopolymer, as well as its complementary use with other polymers, further attract the scientific community, offering improved and combined properties in the final materials. As a result, chitosan has been extensively used as a matrix for the encapsulation of several valuable compounds. In this review article, the advantageous character of chitosan as a matrix for nanosystemsis presented, focusing on the encapsulation of natural products. A five-year literature review is attempted covering the use of chitosan and modified chitosan as matrices and coatings for the encapsulation of natural extracts, essential oils or pure naturally occurring bioactive compounds are discussed.